Terephthalic acid derived ligand‐stabilized palladium nanocomposite catalyst for Heck coupling reaction: without surface‐modified heterogeneous catalyst. (20th July 2016) - K. S., Jithendra kumara; G., Krishnamurthy; B. E., Kumara swamy; N. D., Shashi kumar; Naik, Satish; B. S., Krishna; Naik, Nagaraj
Abstract : A new protocol is reported for the synthesis of a heterogeneous palladium nanocomposite stabilized with a terephthalic acid‐derived ligand ( N, N ‐bis(4‐hydroxy‐3‐methoxybenzylidene)terephthalohydrazide). This is a highly insoluble ligand in common organic solvents, except dimethylformamide and dimethylsulfoxide. The resulting palladium nanocomposite acts as an efficient catalyst precursor for Mizoroki–Heckcoupling reactions conducted under various reaction conditions. The spectral data suggest that the rate, yield and recycling of the catalyst are more effective forC–C coupling reactions . Copyright © 2016 John Wiley & Sons, Ltd. Abstract : We combined heterogeneity and stabilizing power of a terephthalic acid‐derived polydentate ligand in one process. This polydentate ligand is successfully used as a capping agent to stabilize palladium atoms at a very good nano‐size ranging from 5 to 7 nm. This palladium nanocomposite is used as a heterogeneous catalyst for Mizoroki–Heck reaction giving high yield and purity, with good catalyst recovery without loss of activity.